Exploring Discursive and Linguistic Barriers to Social Inclusion through the Lens of Family Traditions in Latino American Poetry - Frak, Amal Nasser (Pedagogika Społeczna Nova, 2025)
This research delves into the intricate tapestry of Latino American poetry, specifically examining the multifaceted dimensions of discursive and linguistic barriers within the context of family traditions. Through an in-depth exploration, the study seeks to unveil how these barriers intersect with and impact social inclusion. The methodology involves a comprehensive analysis of a diverse range of Latino American poems, scrutinizing linguistic nuances and discursive patterns embedded in the portrayal of family traditions. By elucidating the ways in which these elements contribute to or hinder social inclusion, the research aims to shed light on the often-unexplored dynamics shaping the Latino American experience. Key themes revolve around the negotiation of identity, intergenerational communication, and the evolving nature of cultural expression within the poetic realm. By contextualizing family traditions as a pivotal lens, the study unravels layers of meaning that extend beyond the literary, offering insights into the broader socio-cultural implications. The findings not only contribute to our understanding of Latino American poetry but also provide a nuanced perspective on the intricate interplay between language, discourse, and social dynamics. Ultimately, this research serves as a valuable resource for scholars, educators, and policymakers interested in fostering a more inclusive understanding of Latino American experiences. It underscores the importance of recognizing and addressing linguistic and discursive barriers as integral components of the broader discourse on social inclusion within this vibrant literary tradition.